Impaired retrograde transport by the Dynein/Dynactin complex contributes to Tau-induced toxicity. - Butzlaff, M.; Hannan, S.B.; Karsten, P.; Lenz, S.; Ng, J.; Voßfeldt, H.; Prüßing, K.; Pflanz, R.; Schulz, J.B.; Rasse, T.; Voigt, A. (Human Molecular Genetics, 2015)
The gene mapt codes for the microtubule-associated protein Tau. The R406W amino acid substitution in Tau is associated with frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17) characterized by Tau-positive filamentous inclusions. These filamentous Tau inclusions are present in a group of neurodegenerative diseases known as tauopathies, including Alzheimer's disease (AD). To gain more insights into the pathomechanism of tauopathies, we performed an RNAi-based large-scale screen in Drosophila melanogaster to identify genetic modifiers of Tau[R406W]-induced toxicity. A collection of RNAi lines, putatively silencing more than 7000 genes, was screened for the ability to modify Tau[R406W]-induced toxicity in vivo. This collection covered more than 50% of all protein coding fly genes and more than 90% of all fly genes known to have a human ortholog. Hereby, we identified 62 genes that, when silenced by RNAi, modified Tau-induced toxicity specifically. Among these 62 modifiers were three subunits of the Dynein/Dynactin complex. Analysis on segmental nerves of fly larvae showed that pan neural Tau[R406W] expression and concomitant silencing of Dynein/Dynactin complex members synergistically caused strong pathological changes within the axonal compartment, but only minor changes at synapses. At the larval stage, these alterations did not cause locomotion deficits, but became evident in adult flies. Our data suggest that Tau-induced detrimental effects most likely originate from axonal rather than synaptic dysfunction and that impaired retrograde transport intensifies detrimental effects of Tau in axons. In conclusion, our findings contribute to the elucidation of disease mechanisms in tauopathies like FTDP-17 or AD.